O desenvolvimento de capacidades dinâmicas para a transformação digital em empresas de radiojornalismo brasileiras - Fernandes, Karina Ribeiro (2020)
The digital transformation has been considered one of the biggest challenges facing companies today, opening increasing discussions in academic research and contemporary practices. The literature highlights the need to develop new strategies and capabilities for digital transformation and suggests that companies inserted in a dynamic environment are able to better develop their dynamic capabilities, building and renewing skills to respond to changes. This study aims to contribute to the literature by including the perspective of dynamic capabilities for digital transformation, analyzing Brazilian radio journalism companies that responded to market changes, approached consumers and took advantage of digital innovations to create value. Thus, the objective of the study was to identify the dynamic capabilities developed as a result of the strategic efforts aimed at engaging with digital transformation. For this, a theoretical model was developed, and some propositions based on the literature were suggested to assess the phenomenon. Subsequently, multiple case studies were carried out at the four Brazilian radio journalism companies, all with multiplatform transmission. The data were collected through 28 in-depth interviews and the interviewees were chosen because of their involvement in the process of adopting digital innovations. In addition, observation of the work dynamics in the digital age was made and secondary research sources with more than 150 documents about the companies were used, integrating and triangulating information. The research applied the coding technique as a data analysis strategy, seeking to code and find patterns in the collected data. Aiming to preserve the integrity of the replication logic, we performed the cross-case analysis after the within case analysis using the qualitative data processing software Atlas TI. The results revealed that greater proximity to stakeholders through digital innovations, combined with the construction of an innovative culture, the adoption of an interactive workspace that allows the flow of knowledge among teams and interaction with managers for more agile decisions boosted the development of dynamic capabilities. In addition, the research findings bring as a contribution a new microfundament in the transformation capacity of the company, which in this study is called “iterative strategies”, since the strategies are developed and recalibrated during the execution.